LANGUAGE STYLES OF IPHONE ADVERTISEMENT SLOGANS - Rozalina Rozalina (UC Journal: ELT, Linguistics and Literature Journal, 2020)
There were two research problems addressed in this research. The first was to classify and analyze lexical and syntactic features that were contained in iPhone advertisement slogans. The second was to find out what characterizes the uses of lexical and syntactic features in iPhone advertisement slogans. The data were taken from an online iPhone advertisement slogan from the second version to the latest iPhone version recently. This research used a document analysis method and was categorized as qualitative and quantitative research. After classifying and analyzing the data, the researcher calculated the frequency to identity the top three mostly employ in lexical and syntactic features used in iPhone advertisement slogans. The results of the research were there are seven lexical features and seven syntactic features employed in iPhone advertisement slogans and the most three top dominant lexical features are simple vocabulary with 38.4%, hyperbole 21.1%, and potency with 19.2%. The top three commonly used syntactic features are short sentences with 23.5%, present tense with 19.6%, and long noun phrases with 13.7%. Those language styles are used to grab the customers attention.